Lymphoepithelial cyst of the pancreas: can common imaging features help to avoid resection? - Khristenko, Ekaterina; Garcia, Elena Esteban; Gaida, Matthias M.; Hackert, Thilo; Mayer, Philipp; Kauczor, Hans-Ulrich; Klauß, Miriam (Langenbeck's archives of surgery, 2023)
Differentiation of cystic pancreatic neoplasms remains a challenging task for radiologists regarding the main aim of identifying malignant and premalignant lesions.
Gesehen am 29.03.2023